The Perception of the Teachers Towards Virtual Class and Obstacles During Covid-19 Lockdown Phase - Rai, Uttam Sing; Basnet, Hom Bahadur (Journal of Research and Development, 2021)
Virtual class uses computer software and internet to deliver instruction to the students. This eliminates needs for teachers and students to share the physical classroom. Virtual learning is an emerging educational paradigm which is transforming the way students learn. However, this virgin field of research has not been studied rigorously in the context of Nepal. Considering this, the research was carried out to identify the perception of the teacher of Bhojpur Multiple Campus towards virtual class during COVID-19 lockdown phase. The research adopted quantitative design which is based on the teachers who were involved in virtual teaching during COVID-19 lockdown phase. The study applied non-random purposive sampling process to select the sample for gathering data. The researcher found out that the teachers had the positive perception towards virtual class as 68% teachers agreed with the statement that virtual class is suitable solution during COVID-19 lockdown phase because it saves time and effort. The study may contribute to the educators and the teachers who are thinking to formulate policy for applying virtual class during luck down phase when pandemic is overwhelmed across the country like COVID-19.